2018
DOI: 10.3390/nano8121009
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Biogenic Nanoparticles

Abstract: Infectious diseases pose one of the greatest health challenges in the medical world. Though numerous antimicrobial drugs are commercially available, they often lack effectiveness against recently developed multidrug resistant (MDR) microorganisms. This results in high antibiotic dose administration and a need to develop new antibiotics, which in turn requires time, money, and labor investments. Recently, biogenic metallic nanoparticles have proven their effectiveness against MDR microorganisms, individually an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 114 publications
2
89
0
3
Order By: Relevance
“…Bacterial pathogens cause infections that are typically treated using antibiotics [ 1 , 2 ]. Antibiotics are antibacterial agents that inhibit the growth of bacterial pathogens through diffident modes of action ranging from inhibition of enzyme action to interfering with DNA, RNA and protein synthesis [ 3 ]. These processes ultimately result in the disruption of the bacterial cell membrane structure, leading to cell death [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial pathogens cause infections that are typically treated using antibiotics [ 1 , 2 ]. Antibiotics are antibacterial agents that inhibit the growth of bacterial pathogens through diffident modes of action ranging from inhibition of enzyme action to interfering with DNA, RNA and protein synthesis [ 3 ]. These processes ultimately result in the disruption of the bacterial cell membrane structure, leading to cell death [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are antibacterial agents that inhibit the growth of bacterial pathogens through diffident modes of action ranging from inhibition of enzyme action to interfering with DNA, RNA and protein synthesis [ 3 ]. These processes ultimately result in the disruption of the bacterial cell membrane structure, leading to cell death [ 2 , 3 ]. Recent studies have demonstrated that bacterial pathogens are exhibiting resistance against a variety of antibiotics [ 4 ], thereby limiting the effectiveness of these agents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of nanofibers in the biomedical field requires antimicrobial properties for materials. One approach is incorporating inorganic nanoparticles, among which silver nanoparticles (AgNPs) played an important alternative antibacterial agent and have been studied against many types of microbes [27]. Because of their antimicrobial activities, AgNPs have been extensively used for preparing antimicrobial nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found that both AgNPs and AuNPs of nanoparticles inhibited the biofilm formation by Pseudomonas aeruginosa and E. coli at the sub-MIC concentrations of 6.25 mg/ml for AgNPs and 12.5 mg/ml for the AuNPs. Biofilm inhibition at sub-MIC concentrations might be due to the non-lethal damage or the inhibitory effect on the expression of genes related to motility and biofilm formation [20]. A study carried out by Yu et al [21] showed that the AuNPs exhibited antibiofilm activity on P. aeruginosa.…”
Section: Od= Optical Densitymentioning
confidence: 99%